X-ray investigations of phase transition in Bi₂TeO₅ single crystals - Domoratsky, K.V.; Dudnik, E.F.; Katkov, V.F.; Sadovskaya, L.Ya. (Condensed Matter Physics, 1999)
This work is devoted to researching a phase transition in bismuth tellurite single crystals using a high-temperature X-ray analysis method. The cell parameter step-wise changes at 805 ◦C are revealed. Starting from the data obtained we can say that the first-type transition takes place in bismuth tellurite. Ця робота присвячена дослiдженню фазового переходу в монокристалах телуриту вiсмуту методом високотемпературного рентгеноструктурного аналiзу. Виявленi стрибкоподiбнi змiни параметрiв комiрки при 805 ◦С. Виходячи з отриманих даних, можна казати, що у телуритi вiсмуту має мiсце фазовий перехiд 1-го роду.